Day and night grazing by cattle in the Sahel - Ayantunde, Augustine A.; Fernández Rivera, S.; Hiernaux, Pierre H.Y.; Keulen, H. van; Udo, H.M.J. (2002)
The influence of night grazing on feeding behavior, nutrition and performance of cattle was studied. Twenty-four steers weighing 367 kg (SD = 76) grazed either from 0900 to 1900 (day grazers), 2100 to 0700 (night grazers) or 0900 to 1900 and 2400 to 0400 (day-and-night grazers) during 13 weeks. Four esophageally fistulated steers were used in a cross-over design to sample the diet selected during the day and at night. No differences (P > 0.05) were observed in the diet selected in the day or at night. As the season progressed the fiber components of the diet increased (P < 0.01) significantly while nitrogen and in sacco dry matter disappearance declined (P < 0.01). Actual grazing time (min day-1, SE = 16) were 352, 376, and 476 for day, night, and day-and-night grazers, respectively. Day-and-night grazers had a higher intake of organic matter than either day or night grazers. Night grazers had the lowest forage intake and also the slowest rate of consumption. Steers that grazed in the night had the lowest water intake: 22.7 liter day-1 (SE = 1.5) in week 4; 19.9 liter day-1 (SE = 1.1) in week 8. Average weight changes (g day-1, SE = 62) were -435, -548 and -239 for day, night, and day-and-night grazers, respectively. These results show that during the dry season, grazing exclusively in the night cannot substitute for day time grazing, but that it is rather complementary to the latter. Timing (day or night) of grazing did not affect diet selection but nocturnal grazing decreased the need for water.